The effect of elevated temperature and heating duration on high strength concrete with steel slag as cement replacement - Ho, Chia Min (2023)
A vast demand for concrete contributes to an enormous cement production where cement is the primary constituent in concrete manufacturing. Besides, the industry waste such as steel slag (SS) has produced in a large quantity and a large portion of it is disposed of on landfilling which causing a serious environmental impact. Utilization of the SS as partial cement replacement in producing concrete would reduce the cement consumption and amount of waste disposed. In addition, high strength concrete (HSC) is a heterogeneous composite which undergoes a transformation of physical, chemical, and mechanical behavior in a complicated way when subjected to elevated temperatures. The use of industrial by-products as supplementary cementitious materials in HSC has influenced the performance of itself after exposure to high temperature Thus, this research was conducted to investigate the effect of different heating temperatures and heating durations on HSC with the different particle sizes of SS as cement replacement based on the physical, chemical, and mechanical properties. Two different SS particle sizes were used as partial cement replacements which are fine SS (0.075mm) and coarse SS (0.15mm). At the early stage of the research, trial mix was conducted to identify the optimum water-cement ratio and SS replacement ratio. A control specimen and SS-HSC was cast into (100 x 100 x 100) mm cube, and (dia. 100 x 300) mm. After 28 days, the specimens were placed in the electrical furnace at temperature of 200℃, 400℃, 600℃ and 800℃ for 1, 2 and 3 hours. The physicochemical characteristic of the SS-HSC was examined by mass loss, color change, scanning electron microcopy (SEM), X-Ray diffraction (XRD), and thermogravimetric analysis (TGA). While the mechanical properties of SS-HSC were investigated by compressive strength test and modulus of elasticity. Besides, the results from compressive strength test and modulus of elasticity were used in mathematical modelling. In this study, Response surface methodology (RSM) was conducted to develop the mathematical model with various independent and dependent variables. The findings show that microstructure of HSC becomes denser when heated up to 400°C while the microcracks are found when subjected to 600°C and above. The residual compressive strength of SS-HSC is increased up to 400°C and decreased after exposure to 600°C and above. Furthermore, CSS10 obtained slightly higher relative residual compressive strength than FSS10 when heated at elevated temperature. The observed phenomenon could be attributed to the coarser particles size of SS acting as supplementary cementitious materials as well as aggregate in the HSC. From the RSM modelling, HSC subjected to elevated temperatures for 2 hours retains a significantly good performance on the mechanical properties while CSS10 presents a better post-fire behavior as compared to FSS10. The adjusted coefficient of determination (predicted R2) of the models are 0.9648 and 0.9126, respectively. Finally, the study showed that HSC that containing CSS has the potential to be used as structural application in fire resistance.